Carbohydrate‐Based Nanocarriers Exhibiting Specific Cell Targeting with Minimum Influence from the Protein Corona1. Issue 25 (4th May 2015) - Kang, Biao; Okwieka, Patricia; Schöttler, Susanne; Winzen, Svenja; Langhanki, Jens; Mohr, Kristin; Opatz, Till; Mailänder, Volker; Landfester, Katharina; Wurm, Frederik R.
Abstract Whenever nanoparticles encounter biological fluids like blood, proteins adsorb on their surface and form a so‐called protein corona. Although its importance is widely accepted, information on the influence of surface functionalization of nanocarriers on the protein corona is still sparse, especially concerning how the functionalization of PEGylated nanocarriers with targeting agents will affect protein corona formation and how the protein corona may in turn influence the targeting effect. Herein, hydroxyethyl starch nanocarriers (HES‐NCs) were prepared, PEGylated, and modified on the outer PEG layer with mannose to target dendritic cells (DCs). Their interaction with human plasma was then studied. Low overall protein adsorption with a distinct protein pattern and high specific affinity for DC binding were observed, thus indicating an efficient combination of "stealth" and targeting behavior.